THE IMPORTANCE OF EMPIRICAL APPROACH IN COLLECTING LINGUISTIC DATA AND CREATING THE STRUCTURE OF BUKHARA DIALECT - Soliyeva Farida Bobir qizi (Western European Studies, 2025)
The article analyzes the theoretical and practical importance of studying the phonetic, morphological, and lexical features of the Bukhara dialect through an empirical approach. The research results demonstrate the dialect's relationship with the Uzbek literary language, regional and intergenerational differences, as well as its connection with historical and cultural context. Data collected based on empirical methodology serves as an important source in creating the linguistic structure of the dialect and in deep understanding of regional dialects.
Keywords: Bukhara dialect; phonetics; morphology